(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, Mahmudhoja Behbudi, considered the father of Turkestan contemporaries, talks about his activities for the development of his homeland, the widespread promotion of educational ideas in Turkestan, the development of school activities, and the work he did to educate the people. , his publishing and printing activities, the development of education reflected in his articles, the training of advanced national personnel, education, language learning, etc.